1993
DOI: 10.1016/0020-7292(93)90695-s
|View full text |Cite
|
Sign up to set email alerts
|

The tap test: A simple and inexpensive method for the diagnosis of fetal pulmonary maturity

Abstract: The tap test is a reliable, rapid, easy, inexpensive and accurate method for detection of fetal lung maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In another study comparing the Tap test and profile of phospholipids 5 th minute sensitivity was found 90.9%, specificity 91.8%, PPV 50%, NPV was 99.1% (16) . In the evaluation of 5th minute we found that 'Tap test' has a sensitivity of 91%, specificity 88%, PPV 68%, and NPV 97.5%.…”
Section: Discussionmentioning
confidence: 91%
“…In another study comparing the Tap test and profile of phospholipids 5 th minute sensitivity was found 90.9%, specificity 91.8%, PPV 50%, NPV was 99.1% (16) . In the evaluation of 5th minute we found that 'Tap test' has a sensitivity of 91%, specificity 88%, PPV 68%, and NPV 97.5%.…”
Section: Discussionmentioning
confidence: 91%
“…Thereafter many studies have been conducted comparing the tap test and shake test with the standard phospholipids profile to determine the reliability of these tests as compared to the standard tests . [11][12][13][14][15] The ideal test for fetal lung maturity should be rapid, inexpensive, and capable of being done at the patient's bedside, with high predictive value for both positive and negative results. 16,17 Fetal lung maturity can be determined as soon as the baby is born from gastric aspirate at the bedside and can be decided accordingly with the referral of the patients to the higher center where all neonatal facilities are available.…”
Section: Introductionmentioning
confidence: 99%